Secure Data Management in Decentralized Systems - Yu, Ting.; Jajodia, Sushil; SpringerLink (Online service) (Boston, MA : Springer US, 2007)
The research scope of database security has expanded greatly, due to the rapid development of the global inter-networked infrastructure. Databases are no longer stand-alone systems that are only accessible to internal users of organizations. Instead, allowing selective access from different security domains has become a must for many business practices. New data services are emerging every day, which also brings new challenges to protect data security. The internet and the web offer means for collecting and sharing data with unprecedented flexibility and convenience. Secure Data Management in Decentralized Systems identifies and addresses these new challenges. This volume presents a wide range of active areas, closely related to database security by distinguished leaders within this field. Solutions are included. Secure Data Management in Decentralized Systems is designed for a professional audience composed of practitioners and researchers in industry. This book is suitable for graduate-level students in computer science as well.
Foundation -- Basic Security Concepts -- Access Control Policies and Languages in Open Environments -- Trusted Recovery -- Access Control for Semi-Structured Data -- Access Control Policy Models for XML -- Optimizing Tree Pattern Queries over Secure XML Databases -- Distributed Trust Management -- Rule-based Policy Specification -- Automated Trust Negotiation in Open Systems -- Building Trust and Security in Peer-to-Peer Systems -- Privacy in Cross-Domain Information Sharing -- Microdata Protection -- ?-Anonymity -- Preserving Privacy in On-line Analytical Processing Data Cubes -- Security in Emerging Data Services -- Search on Encrypted Data -- Rights Assessment for Relational Data.
Keywords: Computer science; Computer communication systems; Data structures (Computer science).; Data encryption (Computer science).; Database management; Information storage and retrieval; Computer Science; Database Management; Data Structures, Cryptology and Information Theory; Data Encryption; Computer Communication Networks; Information Storage and Retrieval; Information Systems Applications (incl. Internet).; Electronic books